Regulating Criminal Propaganda on Electronic Media in Light of The Afghan Legal Framework: An Analytical Study - Farooqi, Noor Anwar; Bin Daud, Mahyuddin (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
Abstract Criminal propaganda on electronic media is broadcast in contradiction to the Islamic, religious and national values and interests of Afghanistan. The legislation of Afghanistan pressingly criminal propaganda on TV and radio, especially the penal code, the law on crime against internal and external security, and mass media law, although the norms of these laws are general, there is no comprehensive definition and explanation regarding criminal propaganda on electronic media in the legal framework of Afghanistan. Defamatory, hate, false, fake, and rumour propaganda on electronic media are prohibited under the tents and rules of Islamic law and legislation of Afghanistan. This paper aims to explain and regulate criminal propaganda on TV and radio. So that prevent the malicious influences of criminal propaganda in Afghan society. This is because there are numerous forms of criminal propaganda on electronic media namely foreign dramas, films, movies, hatred and false declarations in Afghanistan. The legal issues of criminal propaganda on electronic media in the Afghan legal framework are analytical, explanatory, and illustrative. All legal sides of criminal propaganda have been analyzed and explained under the legislation of Afghanistan. However, international human rights legal documents, Islamic law, and Afghan legislation forbid criminal propaganda to broadcast on electronic media. Due to the non-implementation of law, unprofessionalism of electronic media staff, and weak governance criminal propaganda has been disseminated. Therefore, it is submitted that several powerful regimes have been demolished by broadcasting criminal propaganda on electronic media in Afghanistan. America is the first big and powerful country to broadcast criminal propaganda, it can even be called the father of criminal propaganda.